2022
DOI: 10.1177/23814683221089659
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Survival with Immune Checkpoint Inhibitors and Its Implications for Survival Extrapolations: A Case Study in Advanced Melanoma

Abstract: Background Survival heterogeneity and limited trial follow-up present challenges for estimating lifetime benefits of oncology therapies. This study used CheckMate 067 (NCT01844505) extended follow-up data to assess the predictive accuracy of standard parametric and flexible models in estimating the long-term overall survival benefit of nivolumab plus ipilimumab (an immune checkpoint inhibitor combination) in advanced melanoma. Methods Six sets of survival models (standard parametric, piecewise, cubic spline, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Our study validated several peer studies and guidelines [ 4 , 6 15 , 18 ]. Firstly, models with the best GOF might not necessarily provide improved extrapolation performance.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Our study validated several peer studies and guidelines [ 4 , 6 15 , 18 ]. Firstly, models with the best GOF might not necessarily provide improved extrapolation performance.…”
Section: Discussionsupporting
confidence: 76%
“…Thirdly, external evidence can be helpful to validate the model choice, especially when dealing with immature data. Among previous studies, two have already compared the different extrapolation models through the case study of Checkmate 067 [ 4 , 18 ]. Gibson et al compared RCS with standard parametric models and found that RCS performed better in modeling PFS [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations